Recent advances in the clinical management of intoxication by five heavy metals: Mercury, lead, chromium, cadmium and arsenic - Mahdi Balali-Mood; Nastaran Eizadi-Mood; Hossein Hassanian-Moghaddam; Leila Etemad; Mohammad Moshiri; Maryam Vahabzadeh; Mahmood Sadeghi (Heliyon)
Metals have been used for many centuries, but their nutritional and toxic effects have been investigated since the last century. The common toxic heavy metals (THM) include mercury, lead, chromium cadmium, and arsenic. As human exposure to THM increasingly causes systemic and organ complications, it seems required to review the recent advances of treatment of the toxic metals.Despite the current knowledge of the hazards of heavy metals, there is still high incidents of their poisonings particularly in developing countries. In this review, after an introduction, we briefly describe the routes of exposure, clinical features and prognosis of each metal poisoning. Then, review the different treatments for each metal with particular attention to recent advances in the treatment of both acute and chronic poisonings. The main antidotes for all THM are still chelating agents, but new agents were developed over the past decades and have been used successfully for the THM poisonings. Dimercaptosuccinic acid (DMSA) known as succimer has been prescribed as a safe oral chelator in lead poisoning. Similarly, dimercapto-propanesulfonic acid (DMPS) has also revealed fewer side effects than the old chelating agents. The two are currently gaining increased acceptance among clinical toxicologists. However, there is no specific antidote for mercury poisoning. Dimercaprol is almost no longer used as an antidote of choice in the treatment of chronic THM poisoning.Comparison of clinical management of intoxication by the five heavy metals reveals similar treatment strategies. On the other hand, some of them require specific interventions to reduce the toxicity. Because of drawbacks in the application of commonly known chelating agents, treatment with bioactive compounds which have antioxidant and anti-inflammatory properties has been the subject of much interest in recent research. However, despite the promising results observed in experimental animals, clinical trials on their clinical therapeutic benefits have not been yet successful and need further studies to determine their efficacy and safety in humans. Development of less toxic chelating agents are still under investigations. Moreover, the development of orally administrable chelating agents for home health care would likely be of great interest for future research.